Sobreapreciaç\~oes cambiais e composiç\~ao de comércio exterior nos países emergentes - Marcos Rocha; Nelson Marconi (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– This paper aims at assessing the effects of real exchange rate overvaluation over the export composition for developing countries in a time span of 1970-2004. For this intent, it is estimated an exchange rate overvaluation index by using panel cointegration techniques (Dynamic Ordinary Least Squares (DOLS)). The results show that episodes of overvaluation are negative correlated with manufacturing exports share. In the long run, since such process induces the substitution of domestic for imported manufactured goods, the overvaluation of the TCR can reduce that share in emerging countries.
Keywords: O11; O14; O24; F43; 330; exchange rates; foreign trade; export; emerging countries; Wechselkurs; Kaufkraftparität; Internationale Wirtschaft; Entwicklungsländer; Schwellenländer